Pencegahan Penularan Covid-19 dengan Perilaku Hidup Bersih dan Sehat (PHBS) di Kelurahan Legok Kota Jambi - Putri, Vevi Suryenti; Suri, Marta (Jurnal Abdimas Kesehatan (JAK), 2023)
The Covid-19 pandemic has encouraged people to practice PHBS as the most important part of preventing the spread of the virus. Clean healthy behavior (PHBS) aims to increase the support and active role of health workers, cross-sectoral officers, the mass media, community organizations and leaders, the PKK driving team and the business world. PHBS coaching in households can increase the ability of families to explore health movements in the community. The initial survey which was carried out on March 12 2022 in Legok Village in RT 21, found that most residents did not wear masks, did not practice social distancing, it was seen that some had semi-permanent houses, the average resident's job was construction workers. From these problems, health education is needed about PHBS in preventing Covid-19. The service activity was carried out for 1 day starting with a pre test and ending with a post test regarding knowledge of preventing Covid transmission with PHBS. The results of community service activities show an increase in public knowledge about the transmission of Covid-19 prevention with PHBS by 33%.